Um estudo interdisciplinar da maturidade corporativa para adoção de projetos tecnologicamente viáveis - Seki, Hélio Yasuki (2009)
The term maturity is used in psychology, sociology, biology, technology and other areas of human knowledge. However, a definition related to contemporary needs, in terms of paradigm ruptures that move in the intersections from the Knowledge Age to the Awareness Age, is the focus of this research. In contemporary times, the thinking being , whose thinking ability makes them different from other beings, becomes the main agent to be researched. Consequently, we tried to reach what this research called Corporate Maturity. Departing from the result that was presented in the surveys carried out by the Project Management Institute PMI (an international non-profit entity pioneer in the congregation of professionals of areas related to project management), that there were high levels of failure in technologically feasible projects we tried to find out the relationship between maturity and failure . The immaturity of the thinking being has been defined as the catalyst of the failure experienced by the organizations. Through an interdisciplinary approach, an emerging theory based on the Grounded Theory methodology is suggested, a research methodology over the qualitative paradigm, known as empirical data founded theory. Data were extracted from field work in multiple cases and through the software NVIVO, which consolidated their categorization and saturation and permitted the outlining of a possible emerging theory. Hopefully this paper will help new ones to come up, considering the retraction of the failure rate in the adoption of technologically feasible projects.